Correspondence of Florence O'Donoghue with the Bureau of Military History, - O'Donoghue, Florence, 1895-1967 (1947)
Includes reports of O'Donoghue's activities and correspondence relating to the claiming of expenses, the interviewing of witnesses and requests for leave, mainly conducted with P.J. Brennan.